MRNA Profiling for miR-124-mediated Repair in Spinal Cord Injury. (1st July 2020) - Wang, Jing; Li, Haotian; Chen, Lingqiang; Dong, Junjie; Yang, Jin; Gong, Zhiqiang; Wang, Bing; Zhao, Xueling
Highlights: DE mRNA profiles were identified in SCI rats treated with agomiR-124 by NGS. The molecular functions of the DE mRNAs need further determination. The miR-124/Tal1 axis may participate in the repair of SCI by repopulating NSCs. Abstract: The miRNA miR-124 has been reported to be a promising target for the repair of spinal cord injury (SCI), which is a devastating neurological condition. This study aimed to investigate the underlying molecular mechanisms of miR-124-mediated SCI repair. We established miR-124 SCI model rats and further treated them with agomiR-124 for 14 days. After that, their spinal cords were sectioned, and levels of NeuN, GFAP, and NF-200 were measured via immunofluorescence or via immunohistochemistry. In addition, the spinal dorsal horns were collected for sequencing of total RNA. Differentially expressed (DE) mRNAs were then profiled and a number of these were further verified with qPCR. Gene ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed to predict the potential functions of the DE mRNAs. AgomiR-124 was found to significantly inhibit the decrease of neurons and the activation of astrocytes, while promoting NF-200 expression in the dorsal horn. At fourteen days after agomiR-124 treatment, a total of 85 mRNAs were upregulated and 80 mRNAs were downregulated. We focused our analysis of the DE mRNAs on the top 20 most DE mRNAs, and found four upregulated genes (Nploc4, Yme1l1, LOC103693564, and Aspa) and four downregulated genes (Epb41l2, LOC100911685, LOC100910833, and Smarcc1), which are likely to be of interest to SCI researchers. In addition, we noted that Tal1 is a potential target gene of miR-124, and that a low level of this gene promoted the proliferation of neuronal precursor cells and inhibited their differentiation. In conclusion, miR-124 was able to mediate SCI repair by altering the expression of various mRNAs in rats. The miR-124/Tal1 axis may participate in the treatment of SCI by agomiR-124 by repopulating neural stem cells.